2014
DOI: 10.3201/eid2005.140164
|View full text |Cite
|
Sign up to set email alerts
|

Full-Genome Analysis of Avian Influenza A(H5N1) Virus from a Human, North America, 2013

Abstract: Full-genome analysis was conducted on the first isolate of a highly pathogenic avian influenza A(H5N1) virus from a human in North America. The virus has a hemagglutinin gene of clade 2.3.2.1c and is a reassortant with an H9N2 subtype lineage polymerase basic 2 gene. No mutations conferring resistance to adamantanes or neuraminidase inhibitors were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 14 publications
0
51
0
Order By: Relevance
“…In 2013, a novel 2.3.2.1c reassortant lineage carrying the PB2 gene segment of an Asian lineage H9N2 virus was described for the first time (Pabbaraju et al, 2014 and I101M). In addition, amino acid markers associated with increased virus binding to mammalian receptor type a-2,6-sialic acid (D94N, S133A and S155N) were present in the HA protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, a novel 2.3.2.1c reassortant lineage carrying the PB2 gene segment of an Asian lineage H9N2 virus was described for the first time (Pabbaraju et al, 2014 and I101M). In addition, amino acid markers associated with increased virus binding to mammalian receptor type a-2,6-sialic acid (D94N, S133A and S155N) were present in the HA protein.…”
Section: Discussionmentioning
confidence: 99%
“…The possible transmission routes from Asia to Europe and Africa were not fully understood, but an involvement of migratory wild birds and/or landbased poultry was suspected (Chen et al, 2005; WHO/ OIE/FAO H5N1 Evolution Working Group, 2012). Transspecies transmission of the 2.3.2.1c lineage to mammals has occurred on at least two occasions: a Canadian nurse who returned home from China and fell sick was finally diagnosed with a clade 2.3.2.1c (A/Alberta/01/2014) infection (Pabbaraju et al, 2014); earlier, a tiger in a zoo in China was found positive for that clade (A/tiger/Jiangsu/ 01/2013) (He et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of this H9N2-derived PB2 gene may have occurred in an as-yet-unidentified animal host prior to its transmission to this human case. Whilst birds are most likely hosts for this virus, the possibility of other animal species being an intermediate host transferring this virus to the Canadian patient could not be completely ruled out because the surveillance data for this virus is currently limited, as well as that the investigation has not identified exposure of this Canadian patient to infected avian sources (Pabbaraju et al, 2014). In particular, H5N1 infection in other mammals e.g.…”
Section: Dear Editormentioning
confidence: 94%
“…The recent introduction of a A/H5N1 human infection into North America has again demonstrated the capacity of this virus to cross intercontinental boundaries (Pabbaraju et al, 2014). The release of the full genome sequence has prompted some further analyses of this virus (A/Alberta/01/2014(H5N1); denoted as ALB1 herein) and has suggested a new classification.…”
Section: Dear Editormentioning
confidence: 97%
“…This genotype consisted of a Clade 2.3.2.1c HA (Figure 1) and a PB2 gene derived from H9N2 (Figure 2), with the remaining genes originating from other HPAI H5N1 viruses (Bi et al, 2015a;Monne et al, 2015). It should be noted that the prototype virus of this genotype (A/Alberta/01/2014) was first identified from a Canadian patient who traveled to Beijing, China in December 2013 (Pabbaraju et al, 2014). However, Clade 2.3.2.1c viruses were subsequently identified from wild birds in the central regions of China, the western regions of Russia, Western Asia and Africa along the Central Asian flyway ( Figure 3), suggesting that the novel Clade 2.3.2.1c reassortant viruses are being spread by wild birds along migratory flyways.…”
Section: Phylogenetic Analysismentioning
confidence: 99%